Does Europe perform too little corporate R&D? A comparison of EU and non-EU corporate R&D performance - Pietro Moncada-Paternò-Castello; Constantin Ciupagea; Keith Smith; Alexander Tübke; Mike Tubbs (European Commission, Joint Research Centre (JRC), 2009)
This paper examines whether there are differences in private R&D investment performance between the EU and the US and, if so, why. The study is based on data from the 2008 EU Industrial R&D Investment Scoreboard. The investigation assesses the effects of several very distinct factors that can determine the relative size of the overall R&D intensities of the two economies: these are the influence of sector composition (structural effect) vis-à-vis the intensity of R&D in each sector (intrinsic effect) and the company demographics. The paper finds that the lower overall corporate R&D intensity for the EU is the result of sector specialisation (structural effect) - the US has a stronger sectoral specialisation in the high R&D intensity (especially ICT-related) sectors than does the EU, and also has a much larger population of R&D investing firms within these sectors. Since aggregate R&D indicators are so closely dependent on industrial structures, many of the debates and claims about differences in comparative R&D performance are in effect about industrial structure rather than sector R&D performance. These have complex policy implications that are discussed in the closing section.
Keywords: O33; 330; Research and Development intensity; EU-US R&D gap; size of firms